The evaluation of amino acid profiles of Giant African Snail and Golden Apple Snail as poultry feed supplement - Feshal, Ainzah (2016)
This study was conducted to determine an amino acid profile of two snail Pomacea canaliculata (Golden Apple Snail) and Achatina fulica (Giant African Snail). A 500 g of snails was collected at Bukit Expo, Universiti Putra Malaysia. The analysis of amino acid was conducted in Nutrition Laboratory, Department of Animal Science, Faculty of Agriculture, Universiti Putra Malaysia. These snails were selected because they even now pest of crops. Moreover, the monogastric animal, especially poultry requires more amino acid rather than the ruminant animals. After the snail were collected, the edible part of snails were oven drying at 60ºC for 3 days prior to proximate analysis. The flesh was examined for dry Matter (DM), ash, crude protein contents (CP) and amino acid. Data on DM, ASH, CP and amino acid were analyzed by T test using Statistical Analysis System 9.4 for Windows (SAS Inc., USA). Amino acid was evaluated using Agilent 1100 HPLC. The derivatization process using Agilent 1313A auto sampler. HPLC column that was ZORBAX Eclipse AAA 4.6 x 150 μm PN963400-902. The derivatization reagents consisted of borate buffer, fluorenylmethyl chloroformate (FMOC) and reagent and o-phthalaldehyde (OPA) reagent. The present study showed that the giant African snail contained 69.00% DM, 7.692 ASH, and 57.02 % CP while, the Golden Apple snail has 68.07%DM 7.67% ASH and 56.94% CP. The amino acid content in both snails slightly low and only four amino acid such as aspartate, serine, histidine and isoleusine shows a significant value (P<0.05) in comparing between Golden Apple snails and Giant African snails.